Safety-Oriented Air Quality Index Classification for Imbalanced Data Using Optimized Boosting Models with Optuna and Oversampling - Made Yudi Dwipayana; Gede Angga Pradipta; Dandy Pramana Hostiadi (Universitas Pendidikan Nasional, 2026)
Air Quality Index (AQI) classification is essential for communicating environmental health risks. However, hazardous air conditions occur far less frequently than normal conditions, challenging conventional classification models. This study investigates multi-class AQI classification using the